ETIKA BISNIS ISLAM PADA PEDAGANG MAKANAN - Rahmawati Rahmawati (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2017)
Ethics is the science or knowledge of what is good or what is not good to do, whereas business is defined as an activity that is done by man to earn income or income which is usually called trading. The study aims: to find out how the application of Islamic business ethics to food traders in Keude Blang Jruen. The method that researchers use in this research is qualitative method, while data processing and data analysis begins by reducing the data found in the field, presents the data and draw conclusions. While the sample, the traders in Keude Blang Jruem as many as 30 people. The results show that: The results show that, traders in Keude Blang Jruen, business ethics before everything in accordance with the concept of business ethics as a whole. Every trader sells halal food, whether it is used for making food, or for sale again. As well as not selling goods that kadarluasa, because traders understand the act is prohibited in Islamic business ethics. Merchants sell food by keeping it clean, although there are some less-than-hygienic merchant salespeople, such as not providing trash cans, and there are sellers who rarely clean out their sales. But it is food that is sold clean. Traders sell healthy foods consumed for health. And every trader sells quality food and qualifies MUI even though the merchant has not taken care of halal certification made in MUI. Merchants also have not entirely made legality on trademarks or groceries. The Average traders ini Keude Blang Jreum understand good ethics in trading. Keywords: Food Trade Ethics